Salubrinal in Combination With 4E1RCat Synergistically Impairs Melanoma Development by Disrupting the Protein Synthetic Machinery - Kardos, Gregory R.; Gowda, Raghavendra; Dinavahi, Saketh Sriram; Kimball, Scot; Robertson, Gavin P. (Frontiers in Oncology, 2020)
Increased protein synthesis is a key process in melanoma, which is regulated by the ALDH18A1 gene encoding pyrroline-5-carboxylate synthase (P5CS). P5CS is involved in proline biosynthesis and targeting ALDH18A1 has previously been shown to inhibit melanoma development by decreasing intracellular proline levels to increase the phosphorylation of eIF2 mediated by GCN2 which then impairs mRNA translation. Since there are no current inhibitors of P5CS, decreased eIF2 phosphorylation in melanoma was targeted using salubrinal (a specific inhibitor of eIF2α phosphatase enzymes). While salubrinal alone was ineffective, the combined use of salubrinal and 4E1RCat (a dual inhibitor of eIF4E:4E-BP1 and eIF4E:eIF4G interaction to prevent assembly of the eIF4F complex and inhibit cap-dependent translation) was found to be effective at decreasing protein synthesis, protein translation, and cell cycle progression to synergistically decrease melanoma cell viability and inhibited xenograft melanoma tumor development. The combination of these agents synergistically decreased melanoma cell viability while having minimal effect on normal cells. This is the first report demonstrating that it is possible to inhibit melanoma viability by targeting eIF2α signaling using salubrinal and 4E1RCat to disrupt assembly of the eIF4F complex.